PEMBENTUKAN DAN PENGUJIAN PORTFOLIO SAHAM-SAHAM OPTIMAL: PENDEKATAN SINGLE INDEX MODEL - Putu Anom Mahadwartha; Pranata Yandi Gunawan (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2016)
Buying stock is one of the way investors do to obtain profit from their money. Every investor should consider two important things, return and risk. To minimize the risk, one can diversify their investment by creating optimal portfolio, which consists of different stocks with optimal return and certain degree of risk. The aim of this research was to establish and determine the optimization of optimal portfolio composed by LQ45 stocks over the period of February 2011 to January 2015. The research was trying to create optimal portfolio from thirty-eight non-financial companies stocks listed in LQ45 using single index model. From the research, the optimal portfolio is composed of TLKM (PT Telkom Indonesia Tbk), BMTR (PT Global Mediacom Tbk), JSMR (PT Jasa Marga Tbk), SSIA (PT. Surya Semesta Internusa Tbk), AKRA (PT AKR Tbk), MNCN (PT Media Nusantara Citra Tbk), WIKA (PT Wijaya Karya Tbk), ASII (PT Astra International Tbk), KLBF (PT Kalbe Farma Tbk), ASRI (PT Alam Sutera Realty Tbk), UNVR (PT Unilever Indonesia Tbk), ICBP (PT Indofood CBP Sukses Makmur Tbk), SMGR (PT Semen Indonesia Tbk), and only able to be used for six months. The optimal portfolio gives 0.242% returns for a week with 1.122 value of beta. Majority of the aggressive portfolio have higher return toward risk then portfolio moderate and conservative.